Women's Experiences Following Peripartum Hysterectomy: A Qualitative Study - Sheenu Gahlawat; Monika Dutta; Venkadalakshmi Varatharajaperumal; Pradip Kumar Saha (Tehran University of Medical Sciences, 2024)
Objective: Peripartum hysterectomy is a major operation and is inevitably performed where certain indications require removal of the uterus at the time of delivery or in the immediate postpartum period. It is a traumatic birth event that affects women's physical, physiological, psychological, social, and sexual health. This study aimed to explore the lived experiences of women undergone peripartum hysterectomy. Materials and methods: Qualitative phenomenological design was adopted to explore the lived experiences of women undergone peripartum hysterectomy. Purposive sampling technique was adopted to enroll the participants and 19 women were interviewed before saturation of responses was reached. All interviews were audio recorded and then transcribed into verbatims. Colaizzi's thematic analysis method was used to analyze the data. Results: Based on participants' verbatims eight major themes emerged: Awareness status regarding peripartum hysterectomy; Body's response to peripartum hysterectomy; Perceived need of support; Facilitators in overcoming post-hysterectomy challenges; Relational turbulence; financial burden; Perceived psychological adaptation; Disturbed body image and low self-esteem. Conclusion: Derived themes in the present study highlighted the multidimensional effects of peripartum hysterectomy. Peripartum hysterectomy affected physical, psychological, sexual and financial health of the women. Increased dependence and changes in the self concept are the other problems faced by peripartum hysterectomy women. Need based individualized psychological therapeutic interventions will facilitate the successful adaptation to the traumatic situation by the reinforcement of positive coping mechanisms.